O espírito e a carne: a crítica de Bergson e Merleau-Ponty à ontologia objetivista - Temporal, Vanessa de Oliveira (2019)
The basic aim of this thesis is to investigate the concepts of image in Henri Bergson (1859-1941) and of form in Maurice Merleau-Ponty (1908-1961). Bearing in mind the trajectory that these concepts play on both authors’ works, regarding the plenitude of existence into philosophy, as well as the way by which they are characterized as a counterpoint to the artificiality of abstract symbols, we question ourselves the philosophical potential to approach them. Taking into account their motor and vital natures, could there be a similarity in the way they structure philosophical enquiry? We are going to demonstrate that these concepts come close to each other insofar as they integrate a common project, namely the project of undertaking a phenomenal field and replacing the subject of the transcendental field for life itself as a condition for knowledge.